Implementation of Value Education in Chemistry as an Effort to Develop Character - Ifah Silfianah; Mike Rahayu; Bayu Saputra (Universitas Lampung, 2021)
Implementation of Value Education in Chemistry as an Effort to Develop Character. It has been indicated that there are moral setbacks for the nation's next generation. Therefore, it is necessary to instill values to shape character through education in schools and colleges. This study aims to analyze the values of learning chemistry, find out how educators embed values in learning chemistry and determine the obstacles faced in adding values in chemistry learning. The method in this research was descriptive qualitative using interviews as data collection techniques. The subjects interviewed were six lecturers who taught chemistry at five different colleges and two chemistry teachers who taught at High Schools and Vocational High Schools. The results showed that the character values in learning chemistry can be grouped into religious values, social values, and scientific values. Chemistry teachers or lecturers instill character values by getting them used to reading scriptures before learning, presenting phenomena in daily life related to the chemistry concept, giving independent or group assignments in learning and practicum, and be a good role models. Both teachers and lecturers faced some obstacles in instilling character values in chemistry learning.